IMPROVING THE WEBSITE AS THE MAIN TOOL OF E-BUSINESS - IVANCHENKOVA, LARYSA; TKACHUK, HALYNA; MARKOVA, TETIANA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article defines the essence of e-business, identifies the main forms of trade transactions via the Internet. It is noted that e-business is directly related to information and communication technologies, focused on achieving a specific goal of the business entity, through information technology, and is a specific system. The main types and characteristics of websites as the main tool of e-business are identified: business card site, company website with product catalog, online stores, news search portals, information portals, web-sites of goods accounting, accounting. The main opportunities for using the website to run a business, which allows the company to create and deploy information resources of the organization, accelerate user access to information at any time, conduct advertising campaigns, integrate information resources with resources of suppliers, business partners and global information resources. We analyzed U.S. statistics that prove the value of a website, and say that 85% of people in the world conduct online research on a product or service before reviewing or buying it, and trust online reviews as well as personal recommendations, when As a result, businesses can lose 22% to 70% of potential customers, when placing negative articles on the first pages of search, and before deciding to work with the client, more than half of Americans searched for information on Google. Based on statistics, the most effective methods of improving the website were identified: measuring the effectiveness of the company’s website, improving visibility through search engine optimization, investing in search marketing, improving digital strategy, creating an online plan and personalization.